COVID-19 and the Mental Health Impacts on Oncology Healthcare Professionals: Literature Systematic Review - Ramos, Ana Paula Silveira (2022)
Introduction: The oncological environment, by itself, is a place that often exposes professionals who work there to cope with experiences and suffering in their daily work due to the characteristics of the pathology. Objective: To verify and analyze the evidence of the impact of the coronavirus disease 2019 (COVID-19) pandemic on the mental health of oncology professionals. Method: Search at the databases Web of Science, PubMed, MEDLINE via Ovid, CINAHL via EBSCO and Embase, and evaluation according to the methodology STROBE. Results: A total of 9 articles were included, which highlighted the fragility of the health system worldwide in face of the pandemic, affecting the health of both patients and professionals, especially those who were in the “front line”. These factors provoked high burden of tension, fear, insecurity and professional dissatisfaction. Conclusion: Strategies for the prevention of emotional illnesses related to the specific work of oncology health professionals must be implemented to ensure their mental health.